Improving the Mechanism of Selecting the Next Relay Node on GPSR Routing Protocols in VANET - القبيلي مثنى; حسن بسام (Latakia University Journal -Engineering Sciences Series, 2022)
A Vehicular Ad-hoc Network (VANET) is a collection of nodes forming a wireless network, but the nodes of this network are vehicles with special equipment that enables them to communicate with each other. VANET protocols have to face high challenges due to dynamical changing of topology, and link breakage. A suitable and effective routing protocol helps to ensure that messages are reached to their destination and to achieve the desired aim of the application. In this research, we are working to improve the mechanism for selecting the next relay node in the GPSR Greedy Routing Protocol, by making an improvement to the part related to predicting the future location of nearby vehicles. In order to select the vehicle with the optimal destination, the appropriate location and the appropriate speed, to be the next relay node from the list of neighbors. It passes data packet to it to improve network performance by minimizing lost packets, time delay, and avoiding link breakage.